Backscatter radio communication for IoT applications - Correia, Ricardo (2018)
The so called Internet of Things (IoT) is progressivelybecoming a normal thing in everyone daily lives. Thedesire of connecting everyday objects to the internet and to eachother, to interact with other users and machines, is increasinglybecoming a reality. In this context, where billions of connectedobjects are expected to be ubiquitously deployed worldwide, thefrequent battery maintenance of wireless nodes is undesirableor even impossible. The growth of the devices will be madepossible only if the sensors battery needs are eliminated orreduced significantly. For low power sensors and devices, carefulpower management and power conservation are critical to devicelifetime and effectiveness. One of the possible solutions is tochange completely the paradigm of the radio transceivers in thewireless nodes of the IoT system. The new paradigm should beable to communicate and to enhance the power to the sensor byusing only electromagnetic waveforms transmitted over the air,in order to make the Wireless Power Transfer (WPT) concept areality.